2023
DOI: 10.1038/s41467-023-37206-4
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme-mediated RNA synthesis and replication in a model Hadean microenvironment

Abstract: Enzyme-catalyzed replication of nucleic acid sequences is a prerequisite for the survival and evolution of biological entities. Before the advent of protein synthesis, genetic information was most likely stored in and replicated by RNA. However, experimental systems for sustained RNA-dependent RNA-replication are difficult to realise, in part due to the high thermodynamic stability of duplex products and the low chemical stability of catalytic RNAs. Using a derivative of a group I intron as a model for an RNA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…, the association of substrates). 45–47 Alternatively, as demonstrated for a self-reproducing ligase ribozyme, 48 directed evolution with T G ′ as the parent RNA may also identify highly efficient reproduction of oligonucleotides in a constant environment. It was shown that only a slight difference, including two critical mutations, was sufficient to convert the original ligase ribozyme 13 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, the association of substrates). 45–47 Alternatively, as demonstrated for a self-reproducing ligase ribozyme, 48 directed evolution with T G ′ as the parent RNA may also identify highly efficient reproduction of oligonucleotides in a constant environment. It was shown that only a slight difference, including two critical mutations, was sufficient to convert the original ligase ribozyme 13 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These limitations may be overcome if strong chemical activation is adopted instead of >p or in environments that periodically experience low pH, high temperatures, or low MgCl 2 concentrations, which destabilize RNA-RNA interactions (e.g., the association of substrates). [45][46][47] Alternatively, as demonstrated for a self-reproducing ligase ribozyme, 48 directed evolution with T G ′ as the parent RNA may also identify highly efficient reproduction of oligonucleotides in a constant environment. It was shown that only a slight difference, including two critical mutations, was sufficient to convert the original ligase ribozyme 13 (Fig.…”
Section: Discovery Of a Minimal Self-reproducing Rnamentioning
confidence: 99%
“…For example, moderately acidic pH can protonate the N 1 of adenine and N 3 of cytosine bases, disrupting base pairing and destabilizing RNA duplexes 10 . Coupled with wet/dry cycles or ionic gradients in a thermophoretic setting, this has been shown to promote duplex melting and enable nucleic acid amplification by proteinaceous enzymes 1114 . Furthermore, highly viscous solvents can slow RNA reannealing sufficiently for long (32-nt) substrates to be ligated 15, 16 .…”
Section: Main Textmentioning
confidence: 99%
“…Circumventing full duplex dissociation, strand-displacement syntheses can occur on a short RNA duplex by the progressive addition of “invader” oligonucleotides complementary to the non-templating strand 17 , or by the buildup of conformational strain on circular RNA templates 18 . Despite these advances, the scope of RNA-catalysed RNA replication cycles has been limited: either via polymerisation of NTPs on primers flanking a 4-nt region (assisted by denaturants) 19 , or via templated ligation of (up to) three polynucleotide substrate segments 14, 20 . General RNA replication and open-ended evolution requires both the replication of longer sequences able to encode a phenotype and the polymerisation of building blocks short enough to enable free sequence variation.…”
Section: Main Textmentioning
confidence: 99%
“…A simple way to overcome these issues could be templated ligation, which reduces the number of steps-per-length required to generate an oligonucleotide, and if possible, operating at low magnesium concentration would offer an easier strand separation, particularly when coupled to nonequilibrium microenvironments with salt and pH cycling. 6 Additionally, ligation chain reactions are known to offer exponential replication. 7 The state-of-the-art method for templated ligation makes use of phosphoramidates, such as phosphorimidazolides.…”
Section: ■ Introductionmentioning
confidence: 99%